Vanadium(V) complexes with siderophore vitamin e-hydroxylamino-triazine ligands - Loizou, Maria; Hadjiadamou, Ioanna; Drouza, Chryssoula; Keramidas, Anastasios D.; Simos, Yannis V.; Peschos, Dimitrios (My University, 2021)
Novel vitamin E chelate siderophore derivatives and their VV and FeIII complexes have been synthesised and the chemical and biological properties have been evaluated. In particular, the α-and δ-tocopherol derivatives with bis-methyldroxylamino triazine (α-tocTHMA) and (δ-tocDPA) as well their VV complexes, [V2VO3(α-tocTHMA)2] and [V2IVO3(δ-tocTHMA)2], have been synthesised and characterised by infrared (IR), nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR) and ultra violet-visible (UV-Vis) spectroscopies. The dimeric vanadium complexes in solution are in equilibrium with their respefrctive monomers, H2O + [V2VO2(μ-O)]4+ = 2 [VVO(OH)]2+. The two amphiphilic vanadium complexes exhibit enhanced hydrolytic stability. EPR shows that the complexes in lipophilic matrix are mild radical initiators. Evaluation of their biological activity shows that the compounds do not exhibit any significant cytotoxicity to cells.
Keywords: Vanadium; Vitamin E; EPR; Tocopherol; 51V NMR